2017 IEEE Conference on Computer Vision and Pattern Recognition (CVPR) 2017
DOI: 10.1109/cvpr.2017.253
|View full text |Cite
|
Sign up to set email alerts
|

Light Field Blind Motion Deblurring

Abstract: We study the problem of deblurring light fields of general 3D scenes captured under 3D camera motion and present both theoretical and practical contributions. By analyzing the motion-blurred light field in the primal and Fourier domains, we develop intuition into the effects of camera motion on the light field, show the advantages of capturing a 4D light field instead of a conventional 2D image for motion deblurring, and derive simple methods of motion deblurring in certain cases. We then present an algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 36 publications
0
56
0
Order By: Relevance
“…See [19], [50] for detailed overviews of LF imaging. To date, LF image processing has been applied to a variety of applications including image-based rendering [9], [22], [23], post-capture image refocus [13], [30], SfM [20], lens aberration correction [18], spatial [3] and temporal [46] superresolution, video stabilization [37], motion deblurring [38], and depth imaging [24], [41], [43], [47], [49]. In this work, we explore robust LF feature detection and matching for improving applications in reconstruction including SfM.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…See [19], [50] for detailed overviews of LF imaging. To date, LF image processing has been applied to a variety of applications including image-based rendering [9], [22], [23], post-capture image refocus [13], [30], SfM [20], lens aberration correction [18], spatial [3] and temporal [46] superresolution, video stabilization [37], motion deblurring [38], and depth imaging [24], [41], [43], [47], [49]. In this work, we explore robust LF feature detection and matching for improving applications in reconstruction including SfM.…”
Section: Related Workmentioning
confidence: 99%
“…Light field (LF) imaging is an established tool in computer vision offering advantages in computational complexity and robustness to challenging scenarios [7], [10], [29], [38], [48]. This is due both to a more favourable signal-to-noise ratio (SNR) / depth of field tradeoff than for conventional cameras, and to the rich depth, occlusion, and native non-Lambertian surface capture inherently supported by LFs.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike [23], in this paper, we address the problem of blind deblurring which is a more highly ill-posed problem. Srinivasan et al [26] solved the light field deblurring under 3D camera motion path and showed visually pleasing result. However, their methods do not consider 3D orientation change of the camera.…”
Section: Related Workmentioning
confidence: 99%
“…Note that we use the camera path model used in [19,20]. However, the Bézier camera path model used in [26] can be directly applied to (7) as well. D tm (x, u) is also represented by D tr (x, c) by forward warping and interpolation.…”
Section: Motion Blur Formulation In Light Fieldmentioning
confidence: 99%
“…OF THE PROPOSED DBLRNET. IT IS COMPOSED OF TWO CONVOLUTIONAL LAYERS (L1 AND L2), 14 RESIDUAL BLOCKS, TWO CONVOLUTIONAL LAYERS (L31 AND L32) WITHOUT SKIP CONNECTION, AND THREE ADDITIONAL CONVOLUTIONAL LAYERS (L33, L34 AND L35).EACH RESIDUAL BLOCK CONTAINS TWO CONVOLUTIONAL LAYERS, WHICH ARE INDICATED BY L(X) AND L(X+1) IN THE TABLE, WHERE "X"EQUALS 3,5,7,9,11,13,15,17,19,21,23,25, 27 AND 29 RESPECTIVELY FOR THESE RESIDUAL BLOCKS.…”
mentioning
confidence: 99%